Pengaruh Harga Jual Oli Drum Terhadap Volume Penjualan Pada Pt. Laut Sulindah Luwuk: The Effect Of Drum Oil Selling Prices On Sales Volume At PT. Laut Sulindah Luwuk - Husen, Sri Rahayu (Jurnal Ilmiah Produktif, 2023)
The purpose of this study is to determine the effect of the selling price of drum oil on the sales volume at PT. Laut Sulindah Luwuk. The approach used in this study is a quantitative approach with a data source in the form of secondary data, namely the drum oil sales volume report for the 2020-2023 period. This study uses a simple linear regression analysis technique using the help of the SPSS 16.0 for windows computer program.Based on the results of the study, a simple linear regression equation model was obtained, namely Y = 455.393 – 0.062X, so this model shows that the selling price of drum oil has a negative effect on the sales volume at PT. Laut Sulindah Luwuk for the 2020-2023 period. The value of the correlation coefficient (R) of 0.656 shows that the influence of the selling price (X) of the drum oil used in this equation has a strong influence on the sales volume (Y) and the value of the determination coefficient (R2) of 0.431 shows that the sales volume of 43.1% is influenced by the selling price (X) and the remaining 0.569 or 56.9% is influenced by other variables that are not studied in this study. It was found that the result of a probability value of 0.000 where the significance value was 0.000<0.05 which showed that the selling price (X) of drum oil had a significant effect on the sales volume (Y) which was inversely proportional to PT. Laut Sulindah Luwuk for the 2020-2023 period.